Bartonella species bacteremia in association with adult psychosis - Delaney, Shannon; Robveille, Cynthia; Maggi, Ricardo G.; Lashnits, Erin; Kingston, Emily; Liedig, Chance; Murray, Lilly; Fallon, Brian A.; Breitschwerdt, Edward B. (Frontiers in Psychiatry, 2024)
Introduction The potential role of pathogens, particularly vector-transmitted infectious agents, as a cause of psychosis has not been intensively investigated. We have reported a potential link between Bartonella spp. bacteremia and neuropsychiatric symptoms, including pediatric acute onset neuropsychiatric syndrome and schizophrenia. The purpose of this study was to further assess whether Bartonella spp. exposure or infection are associated with psychosis. Methods In a blinded manner, we assessed the presence of anti-Bartonella antibodies by indirect immunofluorescence assays (IFA), and infection by amplification of bacterial DNA from blood by quantitative polymerase chain reaction (qPCR), digital PCR (dPCR), and droplet digital PCR (ddPCR) in 116 participants. Participants were categorized into one of five groups: 1) controls unaffected by psychosis (n = 29); 2) prodromal participants (n = 16); 3) children or adolescents with psychosis (n = 7); 4) adults with psychosis (n = 44); and 5) relatives of a participant with psychosis (n = 20). Results There was no significant difference in Bartonella spp. IFA seroreactivity between adults with psychosis and adult controls unaffected by psychosis. There was a higher proportion of adults with psychosis who had Bartonella spp. DNA in the bloodstream (43.2%) compared to adult controls unaffected by psychosis (14.3%, p = 0.021). The Bartonella species was determined for 18 of the 31 bacteremic participants, including infection or co-infection with Bartonella henselae (11/18), Bartonella vinsonii subsp. berkhoffii (6/18), Bartonella quintana (2/18), Bartonella alsatica (1/18), and Bartonella rochalimae (1/18). Discussion In conjunction with other recent research, the results of this study provide justification for a large national or international multi-center study to determine if Bartonella spp. bacteremia is more prevalent in adults with psychosis compared to adults unaffected by psychosis. Expanding the investigation to include a range of vector-borne and other microbial infections with potential CNS effects would enhance knowledge on the relationship between psychosis and infection.